The Impact of Biogas Utilization on Poverty in Indonesia - Djoni Hartono; Jayanti Maharani (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2021)
The provision of reliable, adequate, and sustainable energy services has been a global challenge until today. Without the availability of energy, particularly for cooking and lighting, leads to difficulties in achieving the expected quality of life, mainly for underprivileged people who have not met the minimum standard of living. In order to fulfill the necessity of energy, new renewable energy sources are needed, one of which is through biogas installations. The purpose of this study was to find empirical evidence related to the impact of biogas utilization on poverty, especially in rural areas, by transforming the number of underprivileged people in an area. Through Village Potential (Potensi Desa/Podes) data 2008 – 2018, Biogas development from the Ministry of Energy and Mineral Resources in 2011-2017, and using the difference-in-differences (DID) method, it is expected that this study might contribute to the literature, especially related to energy, with comprehensive results. This study detected that after the implementation of biogas installation program, the number of beneficiaries of health insurance programs in villages with biogas installations decreased by 136 people compared to villages without biogas.